Kontrabandos ekonominės prielaidos ir pasekmės - Rimkus, Vladas (Lietuvos statistikos darbai, 2010)
The phenomenon of perpetually existing contraband draws attention of both the public and authorities. This is part of black economy, while black economy itself is a phenomenon that is neither new nor characteristic of a certain economic system. The nature of black economy is destructive as its existence contradicts to public order and interests. Black economy avoids state taxes; therefore, the State – in order to collect funds required for national needs – is forced to increase taxes imposed on those who do pay them. Hence, since some avoid paying taxes, while others assume a heavier tax burden, this results in unequal economic conditions for legal and illegal business and distorts conditions for fair competition. The theoretical study of the problem of contraband is linked to the problem of tax evasion; it reveals stimuli for making a decision not to pay taxes. The decision of each individual to pay or not to pay taxes determines the scope of tax evasion. Adopting a decision not to pay taxes, one faces uncertainty; any individual knows that tax evasion is illegal and subject to punishment in case this comes to light. Therefore, the economics of crime gives initial knowledge about the process of making such decisions. The major part of contraband is comprised of goods subject to excise duties – alcohol, tobacco, and fuel. One of the factors influencing contraband is great difference in prices in Lithuania and neighbouring countries from which contraband comes. For example, contraband cigarettes on the domestic market are approximately three times cheaper than those sold legally. The largest part of these contraband goods comes from neighbouring states – the Russian Federation and Belarus. The main negative consequences of contraband are as follows: a relative reduction in annual government revenue; a general deterioration in economic subordination, which reduces the ability of the government to adopt rational solutions and predict their consequences; insufficient accuracy of provision of social assistance since even those who earn large income from illegal activity may receive it; natural and legal persons tend not to observe existing rules, and the failure to observe the rules may become a norm.